Evaluating Pain Assessment in Emergency Care: A Systematic Review - Jadmiko, Arief Wahyudi; Romadlon, Debby Syahru (Universitas Muhammadiyah Surakarta, 2026)
Effective pain assessment in emergency departments (EDs) is essential to optimizing patient care and improving outcomes such as satisfaction, reduced hospitalization, and lower re-admission rates. This evidence-based critical review aims to explore the relationship between pain assessment practices in EDs and resulting patient outcomes. A systematic search was conducted across three electronic databases—PubMed, Google Scholar, and Web of Science—using the keywords